Aplikasi Acoustic Shells untuk Mendukung Pertunjukan Musik Kamar di Stage Candra Metu ISI Denpasar - Maria Maya Aristya; Ni Wayan Ardini; I Komang Darmayuda (Journal of Music Science, Technology, and Industry, 2022)
Purpose: This article intends to explain the results of using acoustic shells on Candra Metu performance stage at the Indonesian Institute of the Arts Denpasar in an effort to overcome the problem of musicians on stage without using additional PA System. It was intentional so that the quality of the sound’s character authenticity from the acoustic instrument does not change. The acoustical problem in the Candra Metu stage conduces: (1) inadequate sound distribution which were directed to musicians, (2) musicians are not be able to hear between others during the performance. Research Method: The research method used in writing this article is pre-experimental with One-groups pretest-posttest design, which is explained using qualitative-descriptive method with interdisciplinary approach. Results and discussion: The attempt to overcome sound distribution deficient in the Candra Metu stage by testing the acoustic shells as a performance support during chamber music performance. The acoustic shells’ setting and the arrangement of distance between musicians can affect the sound distribution, where the test result shows that by providing panel reflector could affect and increase the sound intensity on the stage. Implication: The application of acoustic shells on the stage can be helpful to increase sound distribution, whereas to obtain the advantage for musician such as clarity on stage, it is necessary to do acoustic simulation in order that the design of acoustic shells can be redeveloped.